Answer:
rearrange them properly to get
x-y=7
-3x+y=12
( by elimination method)
x-y = 7
-3x+y=
(x+ –3x) + (–y+y) = (7+12)
-2x+0= 19
x= -9.5
from eqn(i)
x-y=7
-9.5 - y=7
-y=16.5
y= -16.5
Answer:
1) Distributive Property of Multiplication (The terms are distributed)
2) Addition property of equality (Adding 14 to both sides)
3) Simplifying (We simplified the expression)
4) Division property of equality (Dividing both sides by 6)
Answer:
(4,0)
Step-by-step explanation:
It is a linear function so you find the slope by doing y2-y1/x2-x1 and you find the slope to be 1/2. You can then setup an equation using it and graph it to find the next value.
Answer:
1)y=-3+5x
2)y=5/2-1/2x
Step-by-step explanation:
for both equations
1) get your y by it self (subtract -5x and your new equation is now -y=-5x+3)
2)(reminder y can't be negative if it is negative) then you divide by -1 of both sides
3) your equation should now be y=5x-3
Answer:
the answer would be 48
Step-by-step explanation: